National Webinar for Acute Hepatitis Education in Children for Health Workers and Students in 2022 - Ikbal Fradianto; Nita Arisanti Yulanda; Triyana Harlia Putri; Djoko Priyono (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Acute hepatitis in children that occurred recently in children has an unknown cause. Cases of acute hepatitis in children have also appeared in Indonesia. The number of existing cases is still relatively small, but the incidence of acute hepatitis needs to be addressed as a preventive measure. The problem of acute hepatitis, considered a new case, causes health workers and health students not to have much knowledge regarding this problem. The common understanding of health workers and students regarding recent cases of acute hepatitis in children causes the need to provide information related to acute hepatitis in children. The target focus of this service activity is on health workers and students. Health workers providing health information related to new cases are needed. Technological developments are improving, making health information dissemination more massive. Providing broad information is felt to have a good impact on health workers at large, so national webinar activities related to acute hepatitis in children are felt to provide more comprehensive benefits. This activity was successfully carried out, with a total of 282 participants and 167 who filled out the pre-test and post-test. Participants were attended not only from West Kalimantan but also from various provinces, such as North Sumatra, Java, and others. The average before education is 5.59, which has increased after education to 9.25.